2010
DOI: 10.1021/tx9003819
|View full text |Cite
|
Sign up to set email alerts
|

DNA Modifications by the ω-3 Lipid Peroxidation-Derived Mutagen 4-Oxo-2-hexenal in Vitro and Their Analysis in Mouse and Human DNA

Abstract: 4-Oxo-2-hexenal (4-OHE), which forms a 2'-deoxyguanosine (dG) adduct in a model lipid peroxidation system, is mutagenic in the Ames test. It is generated by the oxidation of omega-3 fatty acids and is commonly found in dietary fats, such as fish oil, perilla oil, rapeseed oil, and soybean oil. 4-OHE also forms adducts with 2'-deoxyadenosine (dA), 2'-deoxycytidine (dC), and 5-methyl-2'-deoxycytidine (5-Me-dC) in DNA. In this study, we characterized the structures of these adducts in detail. We measured the amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…1 Abbreviations: PUFA, polyunsaturated fatty acid; LPO, lipid peroxidation; 4-HNE, 4-hydroxy-2(E)-nonenal; 4-ONE, 4-oxo-2(E)-nonenal; 4-OHE, 4-oxo-2(E)-hexenal; HεdC, heptanone-etheno-2′-deoxycytidine; HεdG, heptanone-etheno-2′-deoxyguanosine; HεdA, heptanone-etheno-2′deoxyadenosine; BεdC, butanone-etheno-2′-deoxycytidine; BεmedC, butanone-etheno-2′-deoxy-5-methylcytidine; BεdG, butanone-etheno-2′-deoxyguanosine; BεdA, butanone-etheno-2′-deoxyadenosine; 8-oxodG, 8-oxo-7,8-dihydro-2′-deoxyguanosine; εdA, 1,N 6 -etheno-2′-deoxyadenosine; 8-OH-AdG, 8-hydroxy-1,N 2 -propanodeoxyguanosine; CdG 2 , R-R-methyl-γhydroxy-1,N 2 -propano-2′-deoxyguanosine;COX-2, cyclooxygenase-2; HPNE, 4-hydroperoxy-2(E)-nonenal; EDE, 4,5-epoxy-2(E)-decenal; 5-LO, 5-lipoxygenase. such as butanone-etheno-2′-deoxycytidine (BεdC), butanoneetheno-2′-deoxy-5-methyl-cytidine (BεmedC), butanone-etheno-2′-deoxyguanosine (BεdG) (19)(20)(21), and butanone-etheno-2′deoxyadenosine (BεdA) (22). The levels of 4-ONE-and 4-OHErelated DNA adducts in humans are currently unknown because such adducts were discovered only very recently.…”
Section: Introductionmentioning
confidence: 99%
“…1 Abbreviations: PUFA, polyunsaturated fatty acid; LPO, lipid peroxidation; 4-HNE, 4-hydroxy-2(E)-nonenal; 4-ONE, 4-oxo-2(E)-nonenal; 4-OHE, 4-oxo-2(E)-hexenal; HεdC, heptanone-etheno-2′-deoxycytidine; HεdG, heptanone-etheno-2′-deoxyguanosine; HεdA, heptanone-etheno-2′deoxyadenosine; BεdC, butanone-etheno-2′-deoxycytidine; BεmedC, butanone-etheno-2′-deoxy-5-methylcytidine; BεdG, butanone-etheno-2′-deoxyguanosine; BεdA, butanone-etheno-2′-deoxyadenosine; 8-oxodG, 8-oxo-7,8-dihydro-2′-deoxyguanosine; εdA, 1,N 6 -etheno-2′-deoxyadenosine; 8-OH-AdG, 8-hydroxy-1,N 2 -propanodeoxyguanosine; CdG 2 , R-R-methyl-γhydroxy-1,N 2 -propano-2′-deoxyguanosine;COX-2, cyclooxygenase-2; HPNE, 4-hydroperoxy-2(E)-nonenal; EDE, 4,5-epoxy-2(E)-decenal; 5-LO, 5-lipoxygenase. such as butanone-etheno-2′-deoxycytidine (BεdC), butanoneetheno-2′-deoxy-5-methyl-cytidine (BεmedC), butanone-etheno-2′-deoxyguanosine (BεdG) (19)(20)(21), and butanone-etheno-2′deoxyadenosine (BεdA) (22). The levels of 4-ONE-and 4-OHErelated DNA adducts in humans are currently unknown because such adducts were discovered only very recently.…”
Section: Introductionmentioning
confidence: 99%
“…HMQC NMR spectrum of dA* is shown in FigureS2(Supporting Information). The 1-hydroxy-hexyl side chain was attached to C-11 of the imidazole ring, as confirmed by the cross-peaks observed between H-1″ and N-1 by 1 H-15 N HMBC.…”
mentioning
confidence: 63%
“…In an animal experiment, higher levels of etheno-type dC and dA adducts were detected in the colon epithelium DNA after the administration of linoleic acid . Various adducts, such as etheno-type-dC, -dA, and -dG adducts, 1, N 2 -propano-type dG adducts, and a malonaldehyde DNA adduct, induced by the lipid peroxidation products, have been measured in animal and human tissues. Chou et al reported that 4-ONE-dA and -dC are the major types of adducts detected in human autopsy tissues . Lipid peroxide-derived DNA adducts were also detected in human gastric mucosa .…”
Section: Introductionmentioning
confidence: 99%
“…Among known DNA adducts that may correspond to [M + H] + = 346, the 2′-deoxynucleoside of butanone-ethenoadenine is a lipid peroxidation-derived lesion that has been detected in vivo and has a molar mass of 345 g mol −1 (Kawai et al. 2010 ). Because the retention time of putative adduct d was nearly the same as the adduct identified as 8-hydroxy-PdG (Table 2 ) it was annotated as either a sodiated adduct of 8-hydroxy-PdG or as a possible butanone-ethenoadenine adduct.…”
Section: Resultsmentioning
confidence: 99%